(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Research on the diversity of multilingual societies: this case study held in eight regions in Indonesia is a study of language attitudes and accommodations. Research data retrieval utilizes a questionnaire that has been prepared. The next step is distributing questionnaires and interviews with native speakers, both regional and Indonesian, in the Special Region of Yogyakarta, DKI Jakarta, Bandung (West Java), Bangka Belitung, South Sumatra, Bali, Lampung, and Banten. The data collection object is speakers of regional and Indonesian languages ​​from academic circles. This diversity research utilizes the theory of attitude and language accommodation, which is implemented from sociolinguistics and pragmatics. The number of respondents in each research area ranges from 20-50 respondents. The research analysis method is descriptive qualitative, and quantitative. The results of the research on the multilingual societies diversity in eight regions in Indonesia show from the qualitative and quantitative analysis that language speakers in eight regions in Indonesia are positive and mutually accommodating between speakers of languages, both using regional languages ​​and Indonesian. The research result is shown qualitatively. For example, Javanese speakers at D.I. Yogyakarta can switch codes or mix codes using Sundanese, Betawi Malay, Madurese, Palembang, Papuan, and other languages ​​. The results of the quantitative analysis also show a very accommodative attitude because it shows a percentage between 41% -62% agree and strongly agree. This diversity research also recommends follow-up research. The correlation test results show that speakers, both local and Indonesian languages, have a moderate correlation of significance—so low that local content education based on regional languages ​​and Indonesian is needed regarding the importance of understanding diversity in a multilingual society. In Indonesia, it can stop the intolerant attitude between language speakers, and even the danger of spreading is the nation’s disintegration.